Implementation of the Education For All Concept in Islamic Educational Institutions - Ade Rosad (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2026)
Education plays a crucial role in human life. However, throughout history, the condition of education in several countries has faced various challenges, particularly in terms of equity and quality. The concept of Education for All emerged as a global initiative to ensure that every individual has access to education without discrimination, regardless of race, social status, or background. This concept strongly aligns with the principles of Islamic education, which emphasise equality, justice, and equal opportunities for learning. This study aims to examine the implementation of the Education for All concept in Islamic educational institutions, both theoretically and practically, and to contribute to the development of literature on inclusive education. The research employs a descriptive qualitative approach with library research as its method. The findings indicate that the principles of Education for All—such as equality, openness, quality, inclusion, and sustainability—are highly relevant to Islamic education. Its implementation within Islamic educational institutions strengthens their role in promoting equitable access to education and enhancing the quality of human resources.